Performance indicators and specifications for fusion-bonded-epoxy(FBE)-coated steel rebars in concrete exposed to chlorides. Issue 2 (4th March 2023) - Kamde, Deepak K.; Zintel, Marc; Kessler, Sylvia; Pillai, Radhakrishna G.
ABSTRACT: Fusion-bonded-epoxy (FBE)-coated steel rebars have been used in many concrete structures in anticipation of better corrosion resistance. However, due to premature corrosion observed, FBE-coated rebars are banned in many parts of the world. On the other hand, such rebars with damaged coating are still used widely in some other parts of the world. This paper discusses the thickness, continuity, flexibility, and chemical composition of coating. Also, the performance indicators such as electrical resistance, UV-resistance, moisture resistance, and chloride diffusion coefficient of coating, and the chloride threshold of FBE-coated rebars are discussed. Laboratory tests adopted techniques (EIS, LA-ICP-MS, and EDX) on samples of coating peeled-off from coated rebars and specimens of coated steel rebars embedded in cement mortar, indicate that more comprehensive and stringent specifications are required to promote the use of quality epoxy materials, FBE-coated steel rebars, and construction practices are recommended.